Enrichment of Exosome-Like Extracellular Vesicles from Plasma Suitable for Clinical Vesicular miRNA Biomarker Research - Moon, Sohee (J Clin Med, 2019)
Exosome-like extracellular vesicles (ELVs) contain biomolecules that have potential as diagnostic biomarkers, such as proteins, micro-RNAs (miRNAs), and lipids. However, it is difficult to enrich ELVs consistently with high yield and purity from clinical samples, which hampers the development of ELV biomarkers. This is particularly true for miRNAs in protein-rich plasma. Hence, we modified ELV isolation protocols of three commercially available polymer-precipitation-based kits using proteinase K (PK) treatment to quantify ELV-associated miRNAs in human plasma. We compared the yield, purity, and characteristics of enriched plasma ELVs, and measured the relative quantity of three selected miRNAs (miR-30c, miR-126, and miR-192) in ELVs using six human plasma samples. Compared with the original protocols, we demonstrated that ELVs can be isolated with PK treatment with high purity (i.e., lack of non-exosomal proteins and homogeneous size of vesicles) and yield (i.e., abundancy of exosomal markers), which were dependent on kits. Using the kit with the highest purity and yield with PK treatment, we successfully quantified ELV miRNAs (levels of 45%–65% in total plasma) with acceptable variability. Collectively, ELV enrichment using the modified easy-to-use method appears suitable for the analysis of miRNAs, although its clinical applicability needs to be confirmed in larger clinical studies.